Analisa Shock Absorber Sepeda Motor dengan Alat Uji Mekanis - Giofani Eko Saputra (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
The use of motorcycles on unstable roads, such as off-road and potholes, demands the importance of a reliable suspension system for riding comfort and safety. Conventional testing of s is often ineffective in accuracy and data recording, so this research proposes the use of an automatic measuring instrument to improve test efficiency and accuracy, allowing users to evaluate deflection in real-time and determine the optimal comfort level. The purpose of this research is to determine the effect of load and brand of motorcycle on deflection value and deflection time. The research method used in this study is the experimental method, which involves a series of trials to collect empirical data related to the characteristics of the . This study uses independent variables in the form of load weight (60 kg, 80 kg, 100 kg) and brand (Aspira, Showa, Kayaba). The measured dependent variables include deflection (mm) and deflection time (s) to evaluate the performance. The results showed that load and brand had a significant effect on deflection and deflection time. Increasing load caused deflection to increase, with Aspira showing deflection of 40-42 mm at 60 kg load and 36-38 mm at 100 kg load. Kayaba had a shorter deflection time of 178.45–180.95 seconds at 100 kg load, compared to Showa's 245.45-275.75 seconds. This shows that Kayaba is more responsive in managing loads, with lower deflection and shorter deflection times than other brands, making it a more effective choice for dealing with varied road conditions.